The Dialogue among Religions around the World: Report on a Workshop - Heisig, James W. (Bulletin of the Nanzan Institute for Religion & Culture, 2005)
On 22 March 2005, representatives from nine countries around the world gathered to present overviews of the current state of religious studies and the dialogue among religions in their respective regions. What follows is a brief account of the workshop, complementing the discussions on the dialogue among religions in the Middle East held the day before. The Nanzan Institute would like to acknowledge the generous support of the Research on Society and Culture of the Suntory Foundation and the Japan Foundation for making these events possible.